Soil organic and inorganic carbon sequestration by consecutive biochar application: Results from a decade field experiment. (20th October 2020) - Shi, Siwei; Zhang, Qingzhong; Lou, Yilai; Du, Zhangliu; Wang, Qian; Hu, Ning; Wang, Yidong; Gunina, Anna; Song, Jiqing
Abstract: Biochar addition can expand soil organic carbon (SOC) stock and has potential ability in mitigating climate change. Also, some incubation experiments have shown that biochar can increase soil inorganic carbon (SIC) contents. However, there is no direct evidence for this from the field experiment. In order to make up the sparseness of available data resulting from the long‐term effect of biochar amendment on soil carbon fractions, here we detected the contents and stocks of the bulk SIC and SOC fractions based on a 10‐year field experiment of consecutive biochar application in Shandong Province, China. There are three biochar treatments as no‐biochar (control), and biochar application at 4.5 Mg ha −1 year −1 (B4.5) and 9.0 Mg ha −1 year −1 (B9.0), respectively. The results showed that biochar application significantly enhanced SIC content (3.2%–24.3%), >53 μm particulate organic carbon content (POC, 38.2%–166.2%) and total soil organic carbon content (15.8%–82.2%), compared with the no‐biochar control. However, <53 μm silt–clay‐associated organic carbon (SCOC) content was significantly decreased (14%–27%) under the B9.0 treatment. Our study provides the direct field evidence that SIC contributed to carbon sequestration after the biochar application, and indicates that the applied biochar was allocated mainly in POC fraction. Further, the decreased SCOC and increased microbial biomass carbon contents observed in field suggest that the biochar application might exert a positive priming effect on native soil organic carbon.